Comparison for ease of insertion for laryngeal mask airway between trendelenburg and supine position for elective orthopaedic, surgical and gynecology surgery - Mohd Nazri, Ali (2008)
The purpose of this study is to assess the ease of insertion of the Laryngeal Mask Airway (LMA) between supine and trendelenburg position in the elective Gynecology, Orthopedic and General surgery patient. We measured easiness of insertion, incidence of adverse respiratory complication and hemodynamic response to LMA insertion. A randomized single blinded prospective study was conducted involving a total of 92 premedicated, ASA 1 or 11 patients, aged 18 to 65 years and were divided into 2 groups either insertion in supine or trendelenburg position. After a standardized induction of anesthesia with Fentanyl 1.5 meg/kg and propofol 2 mg/kg, a size 3 or 4 Laryngeal mask airway was inserted and the patient breathe spontaneously through the surgery with no muscle relaxant given. Anesthesia was maintained with nitrous oxide, oxygen and servoflurance. The LMA was removed at the end of surgery with the patient fully awake. The speed and ease of insertion and the number of attempts needed to successfully secure airway were recorded. The incidence of adverse respiratory complications like sore throat, presence of blood on LMA, laryngospasm, coughing, vomiting and desaturation was recorded. Hemodynamic changes such as systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate at the different time interval were recorded. We found that there was no statistically significant difference in time required for successful insertion and number of attempts for both group. We were able to insert LMA at frrst attempt in 73.9% within 20.20 seconds in trendelenburg position. There were no differences in incidence of adverse airway complication both in supine and trendelenburg position. Both groups had no statistical differences in hemodynamic parameters during spontaneous ventilation under anesthesia except systolic blood pressure and mean arterial pressure just after LMA insertio~ which had statistically significant. We conclude that, insertion of the LMA in trendelenburg position is appropriate provided with a good experience and proper patients selection and strongly indicated in the scenario of fail intubation and ventilation as an alternative to the conventional method of LMA insertion.